Prognostic value of F-18 fluorodeoxyglucose uptake in primary tumor and reticuloendothelial system in patients with head and neck cancer - Demir, Fadime (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the prognostic value of FDG uptake in primary tumor and reticuloendothelial system at 18 Fluorine-fluorodeoxyglucose positron emission tomography / computed tomography (18F-FDG PET / CT) in patients with head and neck cancer.Materials and Methods: A total of 56 head and neck cancer patients who underwent 18F-FDG PET / CT imaging in our clinic for staging were included in study. A circular volume of interest (VOI) was drawn which include tumor tissue on axial images and thereafter SUVmax value of the primary tumor was measured. Bone marrow SUVmax was measured at Lumbal 3-5 th vertebraes. Bone marrow-to-liver uptake ratio (BLR) value was calculated by dividing the bone marrow SUVmax value to liver SUVmax. Bone marrow-to-spleen uptake ratio (BSR) ratio value was calculated by dividing bone marrow SUVmax value to the spleen SUVmax.Results: Forty-five were male and 11 were female of the 56 patients included in the study. The average age was 62.71 ± 14.3. The SUVmax value of primary tumor and age had a significant predictive value in terms of overall survival (p = 0.027 and p = 0.037, respectively). There was a significant difference in overall survival when using 13.6 cut off for SUVmax and 65.5 cut off for age (p = 0.005, p = 0.019, respectively). Age (≥65.5), distant metastasis and SUVmax of primary tumor (≥13.6) values were independent prognostic factors in the multivariate analysis. The bone marrow SUVmax value and BLR and BSR ratios of the patients did not have a significant prognostic value in both univariate and multivariate analysis.Conclusion: The SUVmax value of the primary tumor in 18F-FDG PET / CT in patients with head and neck cancer, had both predictive and independent prognostic value. Bone marrow SUVmax, BLR and BSR values which shows FDG uptake on RES system, were not predictive and prognostic.
Keywords: Head and neck cancer; sup18/supF-FDG PET / CT; FDG uptake of bone marrow; SUVmax